Gaps and needs in the Research and Development Program of the Iloilo State College of Fisheries San Enrique Campus (ISCOF-SEC), Iloilo, Philippines - Genturo, Noel C. (USM R & D Journal, 2010)
To strengthen its R&D program the needs and gaps of the Iloilo State College of Fisheries - San Enrique Campus (ISCOF-SEC) R&D program at San Enrique, Iloilo, Philippines were identified. It also determined the inputs used in the conduct of actual researchers. Using the equation model, it was noted that some of these needs, gaps and inputs were significantly related to R&D performance. Descriptive research design using both qualitative and quantitative data collection and analysis were employed. Some insights were given on how to improve research and development performance as measures of institutional research capability.